A Study of Savonius Wind Turbine Performance with Unsimilar Configuration of Concave and Convex Blade Sides - Mahrous, Abdel-Fattah (Applications of Modelling and Simulation, 2024)
Modifications in classical Savonius rotor have extensively been studied in an attempt to improve turbine performance. The present work investigates experimentally and computationally the effects of combining two different blade shape configurations into a single blade shape design on the Savonius rotor performance. The concave and convex sides of Savonius rotor blade were made unsimilar in shape. Three rotor blades differ in configuration were experimentally and computationally tested including the combined blade. The computational results were primarily validated against experimental data and accordingly a suitable turbulence model was chosen. Among few tested turbulence models, the realizable k-e turbulence model showed closest agreement with the measured data. The results of turbine performance indicate that the combined blade shows better performance than other models particularly at higher tip speed ratios. The maximum power coefficient of the combined blade is increased by about 10% when compared with other investigated rotors. This may be attributed to the blade shape effects on the resulting total drag force. Increasing the maximum power coefficient in addition to the operational range of tip speed ratio are expected when running Savonius turbine with the combined blade.